2007
DOI: 10.4161/hv.3.2.3833
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Production of RNA Transcripts from Individual DNA Plasmids Given in a Multivalent DNA Vaccine Formula

Abstract: We conducted transient transfection studies using two DNA vaccines constructs encoding two Plasmodium falciparum surface proteins, PfCSP and PfSSP2, and UM449 melanoma cells to determine transcription and translation efficiencies. Plasmids were transfected individually or in combination with an empty control plasmid with and without a functional CMV IE promoter. Western blot analysis using NSF1, a monoclonal antibody specific for PfCSP, and UM449 cell lysate revealed an abrogation in expression of PfCSP when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The rationale for multiple antigens was based on the genetic restriction of adaptive cell-mediated immunity: since each malaria antigen provides only limited numbers of strongly-binding class I epitopes for the diverse MHC antigens of the human population, the combination of multiple protective malaria proteins is likely required to achieve broad population coverage 48 . In prior non-clinical studies, we have shown that multivalent DNA vaccines comprising plasmid mixtures can be immunogenic in mice and NHP without significant interference, 16 , 45 , 49 , 73 although plasmids encoding certain malaria proteins could theoretically suppress the immunogenicity of other plasmids if included in the mixture, 50 as shown in vitro 51 …”
Section: Discussionmentioning
confidence: 94%
“…The rationale for multiple antigens was based on the genetic restriction of adaptive cell-mediated immunity: since each malaria antigen provides only limited numbers of strongly-binding class I epitopes for the diverse MHC antigens of the human population, the combination of multiple protective malaria proteins is likely required to achieve broad population coverage 48 . In prior non-clinical studies, we have shown that multivalent DNA vaccines comprising plasmid mixtures can be immunogenic in mice and NHP without significant interference, 16 , 45 , 49 , 73 although plasmids encoding certain malaria proteins could theoretically suppress the immunogenicity of other plasmids if included in the mixture, 50 as shown in vitro 51 …”
Section: Discussionmentioning
confidence: 94%
“…We do not pretend to understand these phenomena. Previously, inhibition between DNA vaccines has been described when the vaccines were given together in the same syringe, and was thought to be due to competition between plasmids within mammalian cells [61][63]. To avoid such competition, we administered each of our DNA vaccine antigens into muscles on different limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines that used plasmid DNA (pDNA) as a physical vector encoding an antigen of interest provided a promising method for preventing diseases such as HIV-AIDS, Ebola, malaria, and cancer (Bacon and Sedegah, 2007;Boyer et al, 2000;Martin et al, 2006) introduced in 1990 when purified DNA was injected intramuscular which yielded both gene expression and biological activity (Jiao et al, 1992;Wolff et al, 1990). Compared with protein vaccines where microgram quantities of the antigen are required, milligram amounts of pure, super coiled pDNA are needed in order to initiate cellular and humoral immune responses (Tavel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%